Isthita’ah Kesehatan Jemaah Haji - Primadatu Deswara (STIKes Persada Husada Indonesia, 2023)
Isthita'ah is the ability of pilgrims physically, and spiritually, with provision, and security to perform the pilgrimage without neglecting their obligations to the family. Isthita'ah health of pilgrims is the ability of pilgrims from a health aspect which includes measurable physical and mental with accountable examinations so that pilgrims can carry out their worship according to the guidance of the Islamic Religion. The research method is a snowball sampling technique and is descriptive in the form of observation, interviews, and documentation. This research seeks to collect existing facts and focus on uncovering a problem in its current state to be studied and studied as a whole. The results of the study can be concluded that the regulation of the Metro City Health Office is based on the Minister of Health Regulation No. 15 of 2016 concerning Health Isthita'ah for Hajj Pilgrims and the process of determining the health isthita'ah for pilgrims who can depart are pilgrims who meet the Hajj health isthita'ah requirements and fulfill the Hajj health isthita'ah requirements with assistance.